NEW RECORDS OF TWO GECKO SPECIES (SQUAMATA: GEKKONIDAE) FROM OUDOMXAY PROVINCE, LAOS - Sitthivong, Saly; Van Ngoan, Ha; Huyen Thuong, Nguyen; Phimphasone, Vilay; Quang Truong, Nguyen; Quang Vinh, Luu (Journal of Forestry Science and Technology, 2020)
Cyrtodactylus wayakonei was originally described from Luangnamtha Province in 2010, Northern Laos, and it was recently reported from Yunnan Province, China. Hemiphyllodactylus kiziriani was described from Luangprabang Province in 2014 and it is currently known only from Laos. This study provides the first records of the two species from Oudomxay Province, Laos based on a new collection of geckos found in the karst forest in Namor District. The new collected specimens of C. wayakonei from Oudomxay Province slightly differ from the original description of Nguyen et al. (2010) by having fewer number of ventral scales from mental to anterior edge of cloacal (152–156 versus 151–163 in type series), fewer precloacal pores in males (6–7 versus 6–8 in the type series). The new collected specimens of H. kiziriani from Oudomxay Province slightly differ from the original description of Nguyen et al. (2014) by having longer snout-vent length (maximum SVL 43.5 mm versus 40.8 mm in the type series), fewer ventral scale rows (11–13 versus 11–15 in the type series), more precloacal pores in males and females (males 13–14 and females 8–12 versus males 10–13 and female 8–10 in the type series, respectively).